Cross Calibration of >16 MeV Proton Measurements From NOAA POES and EUMETSAT MetOp Satellites. Issue 8 (14th August 2019) - Lin, Ruilin; Zhang, Jichun; Redmon, Robert J.; Ni, Binbin; Liu, Siqing; Zhang, Xiaoxin; Shi, Liqin; Gong, Jiancun; Chen, Dong; Cheng, Yonghong; Wang, Hong; Cao, Yong
Abstract: A long‐term data set of energetic proton omnidirectional integral fluxes with an 8‐s resolution from National Oceanic and Atmospheric Administration (NOAA) Polar Operational Environmental Satellites (POES) and EUMETSAT MetOp satellites from 1978 to 2014 has been investigated comprehensively to capture the data bifurcations, calibration inconsistency, and some erroneous data. There are two categories of the data bifurcations. The upper and lower branches of both bifurcations can be clearly separated by magnetic local time or by magnetic latitude. The calibration inconsistency of POES and MetOp proton omnidirectional integral fluxes (>16 MeV) is solved by fitting the data from each pair of two satellites using a third‐degree polynomial function. The fitted curve is almost independent of L m, B / B 0, and time in the valid range. By these fitted functions, the >16 MeV proton omnidirectional integral fluxes from other POES and MetOp satellites are recalibrated to the NOAA‐15 measurements that are adopted as the reference standard. Analyses of the recalibrated data at the geomagnetic equator for about 3.5 solar cycles indicate that the maximal and minimal yearly values of >16 MeV proton omnidirectional integral fluxes are in 1987 and in 2002, respectively. By comparisons with the AP8 model predictions, the ratios of the observations in 1987 (in 2002) to the AP8 MIN (AP8 MAX) predictions are mainly within 0.5‐3 (0.1‐2), showing a dependence on L m and B / B 0 . Key Points: Energetic proton data from NOAA POES and EUMETSAT MetOp satellites need further correction and recalibration for long‐duration scientific studies Compared to rough correction factors regularly used, polynomial functional fits are shown to improve cross calibration Differences between the observations and the AP8 model predictions depend on L m and B / B 0